Association of transfusion transmitted infections with ABO and Rh D blood group system in healthy blood donors: a retrospective analysis - Prakash, Satya; Sahoo, Dibyajyoti; Mishra, Debasish; Routray, Sumansudha; Ray, Gopal Krushna; Das, Pankaj Kumar; Mukherjee, Somnath (International Journal Of Community Medicine And Public Health, 2020)
Background: Transfusion transmitted infections (TTIs) involves several adverse consequences. Studies have shown that ABO blood groups have some association with various infectious and non-infectious diseases. Few blood groups even can act as a receptor and ligand for infectious agents. The objective of the study was to find out any significant association of TTIs with various ABO and Rh D blood group system. Methods: This retrospective study was conducted from July 2016 to October 2018. Blood donors’ blood was tested for ABO and Rh D grouping and five mandatory TTI markers as per Drugs and Cosmetics Act. Chi-square test was performed to look for any association of TTIs with ABO and Rh D blood group. Results: 10,510 healthy donors were screened for TTI and 199 (1.89%) were positive for various TTIs. Hepatitis B had maximum prevalence (102 cases, 0.97%) followed by Hepatitis C (44 cases, 0.41%) and HIV (37 cases, 0.35%). Maximum TTI seroreactive donors were found among ‘B’ blood group (2.21%, 77 cases) followed group ‘A’ donors (2.16%, 53 cases), ‘O’ donors (1.57%, 60 cases) and ‘AB’ donors (1.17%, 9 cases), respectively. However, the risk of association of TTI was not statistically significant with ABO and Rh D blood group. Conclusions: Although no significant association was observed between ABO and Rh D blood groups with TTIs, Hepatitis B was found to be most common infection in blood donors. This high prevalence points towards critical need of comprehensive public health approach to achieve elimination of TTI.